Evolution and diversity of two cisco forms in an outlet of glacial Lake Algonquin - Gabriel Piette‐Lauzière; Allan H. Bell; Mark S. Ridgway; Julie Turgeon (Ecology and Evolution, 2019)
Abstract The diversity of Laurentian Great Lakes ciscoes (Coregonus artedi, sensu lato) arose via repeated local adaptive divergence including deepwater ciscoes that are now extirpated or threatened. The nigripinnis form, or Blackfin Cisco, is extirpated from the Great Lakes and remains only in Lake Nipigon. Putative nigripinnis populations were recently discovered in sympatry with artedi in a historical drainage system of glacial Lake Algonquin, the precursor of lakes Michigan and Huron. Given the apparent convergence on Great Lakes form, we labeled this form blackfin. Here, we test the hypothesis that nigripinnis may have colonized this area from the Great Lakes as a distinct lineage. It would then represent a relict occurrence of the historical diversity of Great Lakes ciscoes. Alternatively, blackfin could have evolved in situ in several lakes. We captured more than 600 individuals in the benthic or pelagic habitat in 14 lakes in or near Algonquin Provincial Park (Ontario, Canada). Fish were compared based on habitat, morphology, and genetic variation at 6,676 SNPs. Contrary to our expectations, both cisco and blackfin belonged to an Atlantic lineage that colonized the area from the east, not from the Great Lakes. Sympatric cisco and blackfin were closely related while fish from different lakes were genetically differentiated, strongly suggesting the repeated in situ origin of each form. Across lakes, there was a continuum of ecological, morphological, and genetic differentiation that could be associated with alternative resources and lake characteristics. This study uncovers a new component of cisco diversity in inland lakes of Canada that evolved independently from ciscoes of the Laurentian Great lakes. The diversity of cisco revealed in this study and across their Canadian range presents a challenge for designating conservation units at the intraspecific level within the framework of the Committee on the Status of Endangered Wildlife in Canada (COSEWIC).